Pulmonary Langerhans cell histiocytosis with inguinal abscess: Unusual presentation. (March 2020) - Mohd Hirmizi, Kamarul Naim; Esa, Nurul Yaqeen Mohd; Abdul Aziz, Mardiana; Bakar, Nor Salmah; Hanafiah, Mohammad
We report a case of a 30-year-old man who was treated as recurrent right inguinal abscess following a 2-month history of right inguinal swelling and intermittent fever with no respiratory symptoms. Resection of his right inguinal lymph node and the histopathological analysis revealed the diagnosis of Langerhans cell histiocytosis. In addition, the CT of the thorax showed presence of bilateral cystic lung changes consistent with pulmonary Langerhans cell histiocytosis.